Can We Notice the Suicidal Warning Signs of Adolescents With Different Psychometric Profiles Before Their Death?: Analysis of Teachers’ Reports - Lee, Mi-Sun; Kim, Joonbeom; Hong, Hyun Ju; Bhang, Soo-Young (Journal of Korean medical science, 2023)
This study aimed to analyze the suicidal warning signs of Korean students with different psychometric profiles based on teacher reports. This was a retrospective cohort study based on Korean school teachers' responses to the Student Suicide Report Form. In total, 546 consecutive cases of student suicide were reported from 2017 to 2020. After missing data were excluded, 528 cases were included. The report consisted of demographic factors, the Korean version of the Strengths and Difficulties Questionnaire (SDQ) for teacher reporting, and warning signs of suicide. Frequency analysis, multiple response analysis, the χ² test, and Latent Class Analysis (LCA) were performed. Based on the scores of the Korean version of the teacher-reported SDQ, the group was divided into nonsymptomatic (n = 411) and symptomatic (n = 117) groups. Based on the LCA results, four latent hierarchical models were selected. The four classes of deceased students showed significant differences in school type (χ² = 20.410, < 0.01), physical illness (χ² = 7.928, < 0.05), mental illness (χ² = 94.332, < 0.001), trigger events (χ² = 14.817, < 0.01), self-harm experience (χ² = 30.618, < 0.001), suicide attempts (χ² = 24.072, < 0.001), depressive symptoms (χ² = 59.561, < 0.001), anxiety (χ² = 58.165, < 0.001), impulsivity (χ² = 62.241, < 0.001), and social problems (χ² = 64.952, < 0.001). Notably, many students who committed suicide did not have any psychiatric pathology. The proportion of the group with a prosocial appearance was also high. Therefore, the actual suicide warning signals were similar regardless of students' difficulties and prosocial behaviors, so it is necessary to include this information in gatekeeper education.